Asymmetric Syntheses of All Stereoisomers of 3-Hydroxyproline; A Constituent of Several Bioactive Compounds - Kumar, Togapur Pavan; Chandrasekhar, Srivari (Synthesis, 2012)
Synthesis of an unusual β-hydroxy-α-amino acid, 3-hydroxyproline, and its derivatives have been achieved enantioselectively by employing Sharpless asymmetric epoxidation and reductive cyclization as the key steps.
Keywords: amino acid; Sharpless asymmetric epoxidation; azido epoxide; reductive cyclization; 3-hydroxyproline